CFD simulations of natural convection heat transfer in enclosures with varying aspect ratios - Pendyala, R. (Italian Association of Chemical Engineering - AIDIC, 2015)
Buoyancy driven natural convection in enclosures has wide range of engineering applications in heat transfer processes. The study of fluid flow and heat transfer characteristics in enclosures has significant importance towards thermal management and optimal design of the systems. Limited studies are available on the numerical simulation of 3-dimensional enclosures with varying aspect ratios (AR). Heat transfer characteristics are investigated in 3D rectangular enclosures with hot and cold surface by computational fluid dynamics simulations at low (0.125) to high (150) aspect ratios (Height/Length). CFD simulations are performed with different fluids at a temperature range of 20 K â¤ ÎT â¤ 100 K and Prandtl number range of 0.01 â¤ Pr â¤ 4,500. The velocity and temperatures profiles in the enclosures are presented. Heat transfer coefficients are estimated for all cases. Correlations for Nusselt number (Nu) based on predicted findings have been developed to represent heat transfer characteristics. Copyright Â© 2015, AIDIC Servizi S.r.l.,.